The Janus-faced role of TRPM2-S in retroperitoneal liposarcoma via increasing ROS levels - Xiangji Li; Fanqin Bu; Shixiang Ma; Ferdinando Cananzi; Yu Zhao; Mengmeng Xiao; Li Min; Chenghua Luo (Cell Communication and Signaling, 2022)
Abstract Background Retroperitoneal liposarcoma (RPLS) is a specific soft tissue sarcoma with a high recurrence rate. The short isoform of transient receptor potential cation channel subfamily M member 2 (TRPM2-S) plays an important role in the regulation of reactive oxygen species (ROS). However, the association between TRPM2-S and RPLS and its underlying mechanisms remains unclear. Methods The expression of both TRPM2-S and TRPM2-L in RPLS tissues was verified by kimmunohistochemistry (IHC). The regulation on Ca2+ influx by TRPM2-S was evaluated by Fluo-4 AM staining. The effect of TRPM2-S on cell proliferation and apoptosis was tested by 5-Ethynyl-2′-deoxyuridine (EdU) staining and Flow cytometry respectively. The level of cellular ROS was assessed by the DCFH-DA probe. Different concentrations of H2O2 were used to provide oxidative stress on RPLS cells. The underlying mechanisms were further explored by Western blotting. Results The IHC assays showed that TRPM2-S, but not TRPM2-L, was prognostic in RPLS. Low TRPM2-S level was associated with poor disease-free survival (DFS). Calcium influx signal intensity was significantly decreased under TRPM2-S overexpression, which resulted in a decrease in the levels of FOXO3a and PTEN. Correspondingly, the levels of pERK, pAKT, pP65, pGSK-3β, Bcl-2, and β-catenin were upregulated, and cellular ROS was gently increased under TRPM2-S overexpression. Moreover, TRPM2-S slightly promoted cell proliferation and inhibited apoptosis of RPLS cell lines under normoxia, but largely increased apoptosis rates under oxidative stress. The cleaved caspase3 was significantly upregulated by TRPM2-S overexpression under oxidative stress. N-Acetyl-l-cysteine (NAC), a small molecule antioxidant, could largely rescue RPLS cells from the apoptosis induced by H2O2. Conclusion TRPM2-S exerts Janus-faced effects in RPLS by increasing the ROS levels via inhibition on FOXO3a, which promotes cell proliferation under normoxia but induces apoptosis under oxidative stress. Video abstract